2016
DOI: 10.1016/j.socscimed.2016.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Power and the association with relationship quality in South African couples: Implications for HIV/AIDS interventions

Abstract: Introduction Power imbalances within sexual relationships have significant implications for HIV prevention in sub-Saharan Africa. Little is known about how power influences the quality of a relationship, which could be an important pathway leading to healthy behavior around HIV/AIDS. Methods This paper uses data from 448 heterosexual couples (896 individuals) in rural KwaZulu-Natal, South Africa who completed baseline surveys from 2012–2014 as part of a couples-based HIV intervention trial. Using an actor-pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 67 publications
5
62
0
Order By: Relevance
“…This is consistent with the results of research conducted by Juang .M At All, in Sub-Saharan Africa, which got the results that health education has a positive effect on public awareness about HIV / AIDS and increased knowledge about the modes of transmission and prevention of HIV / AIDS [8]. The study results Amy A. Conroy [10] to increase HIV-related behaviour should consider the resources together in pairs and point maximum potential for empowerment at the level of partner. Efforts to just focus on the empowerment of women.…”
Section: Resultssupporting
confidence: 90%
“…This is consistent with the results of research conducted by Juang .M At All, in Sub-Saharan Africa, which got the results that health education has a positive effect on public awareness about HIV / AIDS and increased knowledge about the modes of transmission and prevention of HIV / AIDS [8]. The study results Amy A. Conroy [10] to increase HIV-related behaviour should consider the resources together in pairs and point maximum potential for empowerment at the level of partner. Efforts to just focus on the empowerment of women.…”
Section: Resultssupporting
confidence: 90%
“…She suggests that efforts should be made to take the dyadic environment into consideration as well as men's perspectives to ensure positive relationship and health outcomes. [37] We found that the ‘couple’ in our setting, was often a polygamous one, and thus, sometimes one couple member would cite a third person as the potential source of infection. Often, a wife would mention that she knew the HIV-status of her co-wife, but in other couples, a participant would simply say she didn’t know the risks her husband was taking when not at home.…”
Section: Discussionmentioning
confidence: 99%
“…The co‐occurrence of sexual abuse and HIV risk in African women has been attributed to relationship power disparity, as well as cultural norms about discussing sexual issues (Airhihenbuwa & Webster, ; Conjoh, Zhou, & Xiong, ; Conroy et al, ). In the context of an HIV/AIDS epidemic, we need to gain a better understanding of cultural practices influencing African girls and their experience of abuse.…”
Section: Introductionmentioning
confidence: 99%